Special Section on Full-Duplex Transceivers for Future Networks: Theory and Techniques - Tran, Nghi H.; Suraweera, Himal A.; Riihonen, Taneli; Reiskarimian, Negar; Jain, Hardik; Schober, Robert (IEEE Open Journal of the Communications Society, 2021)
Conventional wireless communication systems operate in a half-duplex mode, i.e., current radios cannot transmit and receive at the same time and on the same frequency. Full-duplex wireless operation was generally assumed to be impossible due to the great difference in transmit and receive signal power levels. However, recent advances in antenna, hardware, and signal processing techniques have shown that full-duplex operation is practically feasible. Thanks to novel combinations of antenna, analog, and digital cancellation techniques, self-interference suppression of 80-110 dB can be made possible. The feasibility in building a practical full-duplex radio using off-the-shelf hardware and software-defined radios therefore alleviates many problems in wireless network design.
CRIS-Team WoS Importer:2021-11-26